Performance of Waste Water Treatment Plans in Hospitals : Literature Review - Putra, Heri Shatriadi Candra; Rashid, Norhashima Abd; Said, Faridah Mohd (Asosiasi Guru dan Dosen Seluruh Indonesia, 2023)
Introduction: Hospitalrecyclingwhich cannot function normally and there are calculation errors in thewater mass balanceTo minimize the impact of waste water on environmental pollution, an evaluation of the IPAL unit is carried out. The aim of this research is to evaluate the IPAL and provide suggestions related to optimizing wastewater treatment at Hospital to improve wastewater removal performance. Material and Methods: This study refers to design criteria and quality standards based on literature review with PICO Analysis and evaluation of existing conditions using secondary and primary data. Based on the results of the Wastewater Treatment Plant (WWTP) evaluation, it was found that the waste water discharge was 166.3 m3/day, had an efficiency that was in the very efficient and efficient category in processing waste water pollutant parameters so that the waste water treatment process ran well, and there was equalization of the first and second settling tanks. , activated sludge, trickling filter, filtration, disinfection and recycling did not meet the design criteria so recalculations were carried out.. Results: The solution provided is to tighten monitoring and testing of the condition of the quality of wastewater coming out of the WWTP unit by changing the sampling test method, re-measuring the quality of influent wastewater, improving the workings of the IPAL unit according to the applicable Standart Operation Procedure (SOP). Conclusion: After evaluating the waste water treatment unit, conclusions can be drawn, among others, based on the results of water quality tests and the work performance of the waste water quality parameters. The waste water quality parameter degradation efficiency is very effective, effective and quite effective and all parameters tested are in accordance with applicable quality standards.